The arbitration act 2005: emerging issues on the extent of intervention by Malaysian courts in matters relevant to international arbitration / Aloysius Cornelius Susek ...[et al.] - Susek, Aloysius Cornelius; Nor Azizi, Effa Farida; Ahmad Johari, Faiznur Yazreen; Azlan, Haziq (2011)
Arbitration is one of the forms of alternative dispute resolution and the Arbitration Act 2005 and the New York Convention is used to govern the arbitration in Malaysia. This research is done to raise issues in the Malaysian Arbitration Act 2005 on certain areas specifically on the court intervention in arbitration proceeding which the seat is outside Malaysia, the recognition of awards in international arbitration where the seat of arbitration is in Malaysia and also the interpretation of section 51(2) of the Arbitration Act 2005 and its applicability. This research is set out to provide information on several loopholes in the Arbitration Act 2005 and since there are not many sources of Arbitration in Malaysia, comparison was done with other countries to know their position. Its significance is to help improving the current law of arbitration in Malaysia. Throughout this research, it was found that there are quite a number of loopholes and it is hoped that the current law on arbitration will be more effective and friendly so that the parties to arbitration will not face major difficulties.